Structural Interpretation of Rocks in Igarra, Southwestern Nigeria, using Very Low Frequency (VLF) Electromagnetic Method - Kelechi, Ihekoronye Kingsley; Onuegbe, Ole Moses; Ezenwo, Obioha Young; Iheanyichukwu, Opara Alexander; Njoku, Okereke Chikwendu (Journal of Advanced Research in Geo Sciences & Remote Sensing, 2021)
Structural interpretation of rocks in Igarra area, southwestern Nigeria, to delineate geologic discontinuities such as fractures, joints, faults and basement depressions are carried out in this study. Geophysical studies carried out using Very Low Frequency (VLF) electromagnetic method showed that the basement was highly affected by various structural deformations. These structures originated during the pan African Orogeny. In the reconnaissance mode, VLF profiles can be run quickly to identify anomalous conductivity of rocks. It may be used whenever an electrical conductivity contrast is present between geological units. This may include fault mapping, groundwater investigations, overburden mapping, contaminant mapping and mineral exploration. The electromagnetic anomaly amplitudes are more influenced by the conductivity of the overburden or weathered layer, than the overall thickness. Three profiles were covered and interpreted using Microsoft excel and RAMAG. Exe software to delineate the structural features, which played prominent roles in hydrogeological applications, especially in Basement Complex environments because, they usually act as good groundwater accumulation zones in such environments but catastrophic to engineering geology and constructions. How to cite this article: Onuegbe OM, Ezenwo OY, Iheanyichukwu OA. Structural Interpretation of Rocks in Igarra, Southwestern Nigeria, using Very Low Frequency (VLF) Electromagnetic Method. J Adv Res Geo Sci Rem Sens 2019; 6(3&4): 39-54.